1950
DOI: 10.1111/j.1365-2672.1950.tb05038.x
|View full text |Cite
|
Sign up to set email alerts
|

Routine Resazurin Test Results and Thermoduric Bacterial Content of Milk Samples as a Measure of Milk Production Conditions

Abstract: The milk production conditions on 44 farms (18 designated and 26 non‐designated) have been assessed by score‐card marks for visual conditions, facilities, equipment, and methods. Over a period of one year fortnightly samples from these farms were subjected to routine resazurin tests and laboratory pasteurized counts. The results were compared with the total score‐card marks and the equipment assessments of the farms. It was found that neither test alone sufficed to detect unsatisfactory production, but failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1967
1967
1967
1967

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Figure 1 illustrates the comparative size of colonies produced by M. A thermodurlc count in excess of 10,000 per ml. has been suggested (16,29,57) as providing evidence of unsatisfactory milk production methods. On the basis of this standard, it is noteworthy that in this study, 4-5 percent of the samples which met this standard when plates were incubated at 35° C. for 2 days failed to meet the standard when plates were incubated at 28° C. for 3 days.…”
Section: Effect Of the Various Plating Procedures Upon Colonymentioning
confidence: 99%
“…Figure 1 illustrates the comparative size of colonies produced by M. A thermodurlc count in excess of 10,000 per ml. has been suggested (16,29,57) as providing evidence of unsatisfactory milk production methods. On the basis of this standard, it is noteworthy that in this study, 4-5 percent of the samples which met this standard when plates were incubated at 35° C. for 2 days failed to meet the standard when plates were incubated at 28° C. for 3 days.…”
Section: Effect Of the Various Plating Procedures Upon Colonymentioning
confidence: 99%
“…was indicative of a build-up of thermoduric organisms on parts of the utensils or equipment. McKenzie _et al (57) suggested that thermoduric counts of raw milk exceeding 10,000 per ml.…”
mentioning
confidence: 99%
“…Unidentified bacteria, showing characteristics dissimilar to those of the more common thermodurlc bacteria also contributed substantially to increased counts for some samples upon extended plate incu bation at 35° and 32° C. Again, these organisms may have been overlooked by other workers due to failure to incubate plates for a sufficient period of time.A thermodurlc count in excess of 10,000 per ml. has been suggested(16,29,57) as providing evidence of unsatisfactory milk production methods. On the basis of this standard, it is noteworthy that in this study, 4-5 percent of the samples which met this standard when plates were incubated at 35° C. for 2 days failed to meet the standard when plates were incubated at 28° C. for 3 days.…”
mentioning
confidence: 99%